2004
DOI: 10.17796/jcpd.28.3.gt48634942137234
|View full text |Cite
|
Sign up to set email alerts
|

Panoramic radiographic findings of the mandibular foramen from deciduous to early permanent dentition

Abstract: The purpose of this study was to investigate the position of the mandibular foramen from deciduous (Hellman's stage IIA) to early permanent dentition (Hellman's stage IVA). Panoramic radiographs of 311 Taiwanese children were used. The results revealed that the distances between the mandibular foramen and ramus anterior plane were greater than those between the mandibular foramen and ramus posterior plane through all stages. The mean difference between them was the smallest (0.25 mm) in stage IIA and the great… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
42
1
11

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(62 citation statements)
references
References 8 publications
8
42
1
11
Order By: Relevance
“…Nevertheless, the results of both the studies are similar but not identical. Similarly, the present results are also in accordance but not identical with Tsai (2004) who studied the MF position from deciduous to early permanent dentition on 311 panoramic radiographs of Taiwanese children. It was concluded that through all stages, the MF is located at the posterior half of the ramus and moves anteriorly by 1.5 mm from deciduous to permanent dentition.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Nevertheless, the results of both the studies are similar but not identical. Similarly, the present results are also in accordance but not identical with Tsai (2004) who studied the MF position from deciduous to early permanent dentition on 311 panoramic radiographs of Taiwanese children. It was concluded that through all stages, the MF is located at the posterior half of the ramus and moves anteriorly by 1.5 mm from deciduous to permanent dentition.…”
Section: Discussionsupporting
confidence: 90%
“…In contrast, the posterior ramus had two growth spurts: between stages 1 and 2 and between stages 3 and 4. In contrast, Tsai (2004) found only one growth spurt in the posterior ramus, which occurred after the permanent mandibular second molars erupted.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Alterations in mandibular foramen position during skull growth (Tsai, 2004), presence of accessory nerves to the mandibular teeth (Clark et al, 1999), incorrect anesthetic technique or variability of mandibular foramen position (Nicholson, 1985;Afsar et al, 1998;Mbajiorgu, 2000;Oguz and Bozkir, 2002) can determine failure of IAN block. Hayward et al (1977), after evaluating Asiatic and white and black American skulls, described the location of the mandibular foramen at the third quadrant of the mandibular ramus along its anterior-posterior axis.…”
Section: Introductionmentioning
confidence: 99%
“…하악공에 가깝게 마취액 을 주입하는 것이 중요하지만, 하악공은 촉진이 어려운 내부 구 조물이므로 그 위치를 평가할 수 있는 또 다른 기준점의 표준화 가 필요하다 [2][3][4] . 지금까지 파노라마 방사선 사진과 두부 방사선 사진을 이용 한 하악공의 위치에 대한 연구는 많이 이루어졌다 1,[5][6][7][8][9][10] . 하악공 이 하악지 중앙의 바로 후방부에 위치하거나 1,9) , 하악지의 후방 3/4에 위치한다는 연구 결과 10) 등 다양한 결과들을 보여주었다.…”
unclassified